2021
DOI: 10.3389/fpsyg.2021.606847
|View full text |Cite
|
Sign up to set email alerts
|

Need for Cognition Is Positively Related to Promotion Focus and Negatively Related to Prevention Focus

Abstract: Need for cognition (NFC) and regulatory focus (RF) are important variables with individual differences relevant to motivation and goal pursuit. These constructs are widely used in the literature, often separately; no work has simultaneously examined the need for cognition scale (NCS) and Lockwood’s general regulatory focus measure (GRFM). Here, we explore shared theoretical underpinnings of the two constructs and assess whether they may be driven by common underlying factors. Considering purported overlaps bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(121 reference statements)
0
5
0
1
Order By: Relevance
“…Responses were given on 9-point scales (1 = Not at all true of me to 9 = Very true of me). Analyses of publicly available data from recent research showed strong correlations between the prevention focus item we used and its composite score, r = .60, p < .001, and between the promotion focus item we used and its composite score, r = .74, p < .001 (Oiknine et al, 2021). Higher scores indicated a greater focus on prevention or promotion goals.…”
Section: Regulatory Focusmentioning
confidence: 88%
“…Responses were given on 9-point scales (1 = Not at all true of me to 9 = Very true of me). Analyses of publicly available data from recent research showed strong correlations between the prevention focus item we used and its composite score, r = .60, p < .001, and between the promotion focus item we used and its composite score, r = .74, p < .001 (Oiknine et al, 2021). Higher scores indicated a greater focus on prevention or promotion goals.…”
Section: Regulatory Focusmentioning
confidence: 88%
“…Much is already realized about individuals’ prevention regulatory focus and its compulsion, a series of studies have probed the sources, such as intrapersonal pressure, reputational concerns, autonomy support management, and so forth (e.g., Worthy et al, 2009 ; Pfattheicher, 2015 ; Lai et al, 2018 ; Oiknine et al, 2021 ). Conclusions from numerous researches demonstrated that people with prevention regulatory focus invest time, energy and efforts fully into their duties and obligations and subsequently, beget a sense of security ( Worthy et al, 2009 ; Lai et al, 2018 ).…”
Section: Theory Review and Hypothesesmentioning
confidence: 99%
“…They are more sensitive to negative information, value their reputation and external image, avoid failures and potential losses as much as possible, and prefer to adopt avoidance-based strategies in their behavioral strategies to obtain performance and protection [46]. In the process of running a business, the CEO takes the minimum goal to achieve profitability [19]. When CEOs with prevention focus traits conduct innovative searches, they apply their resources to familiar areas to the greatest extent possible.…”
Section: Ceo Prevention Focusmentioning
confidence: 99%
“…Although CEOs are actively involved in the strategic choices of their firms [16] and the trade-offs between risk-taking and conservatism, studies examining the impact of CEOs' regulatory focus on firms' strategic choices remain scarce, implying that the impact of CEO regulatory focus on strategy may be underestimated. The innovation search behavior studied in this work is divided into depth search and breadth search behavior, both of which require CEOs to trade-off between innovativeness and riskiness [17][18][19]. From this, we propose that CEO regulatory focus may influence firms' search behavior choices in the face of the same positive performance feedback.…”
Section: Introductionmentioning
confidence: 99%